Effects of 4-Week Intervention with Ulmus macrocarpa Hance Extract on Immune Function Biomarkers in Healthy Adults: A Randomized Controlled Trial. (25th February 2018) - Cho, A Ra; Lee, Sang Yeoup; Cho, Young Hye; Kim, Cheol Min; Kim, Sung Goo
Abstract : Ulmus macrocarpa extract has been shown to have immune-related effects in animals, but no studies have yet been performed in humans. This randomized, double-blind, placebo-controlled trial was conducted to determine the effect of short-term administration of Ulmus macrocarpa Hance extract (UME) on immune function biomarkers and its safety in human subjects. Fifty-eight subjects were randomly assigned to a UME group or a placebo group. Subjects in the UME group were given 500 mg per day of UME orally for 4 weeks. Mean fluorescence intensity (MFI) of tumor necrotic factor- α increased only in the UME group at 1 week ( P = 0.027 ) . The MFI of interleukin-2 decreased less significantly in the UME group than in the placebo group at 1 week ( P = 0.028 ) . However, unfortunately, at 4 weeks, no intergroup differences were detected in MFIs of cytokine. In conclusion, administration of UME for 1 week increased serum TNF- α and sustains IL-2 in human, which suggests that UME increases Th1-related immune function in the short term in healthy people. However, additional studies are needed to confirm the results of this first-stage study and further trials are required to decide on optimal dosage and duration of administration. This trial is registered with ClinicalTrials.gov Identifier: NCT02414412 .